การนำกระดูกปลาโอแถบ Katsuwonus pelamis มาใช้เป็นแหล่งแคลเซียมในอาหารว่าง - เอกชัย จารุเนตรวิลาส (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
The tuna bone preparation and application of the treated bone in snacks was studied. Cookies and caramel snack were chosen as snacks in this study. The chemical composition of the bone after washing (cleaning) were 24.48% calcium and 10.12% phosphorus. The bone was treated with steam at 120 ํC 125 ํC and 130 ํC for 30 40 50 and 60 ํC min before grinding. The result showed that heating at 130 ํC for 30 min was the best condition to soften the bone. After steam treatment the bone was dried at 50 ํC 60 ํC and 70 ํC for 1 1.5 2 2.5 and 3 hr in the tray dryer. The dried bone, which moisture content was less than 8%, was ground and passed through 70 mesh screen. It was found that drying at 60 ํC for 1.5 hr was the best condition. The pulverized bone was packed in OPP/Metallized/PP under vacuum condition and could be stored for 11 months. The ground tuna bone at particle size of 50 60 and 70 mesh was supplemented into the cookies at level of 40 and 50% by flour weight. The supplementary cookies had higherresistance force and density but lower spread ratio. Addition of 50 mesh tuna bone at 50% by flour weight resulted in the acceptable product with 3.12% calcium and 2.02% phosphorus. The ground tuna bone at particle size of 50 60 and 70 mesh was also added to Thai caramel snack at the level of 10 and 20% by flour weight. The product with the addition of 50 mesh particle size at 20% by flour weight was acceptable and it had 2.03% calcium and 1.08% phosphorus.